The food and cooking of Malaysia & Singapore : discover an exotic cuisine that blends Malay, Indian and Chinese traditions, with 80 recipes and over 300 photographs - Basan, Ghillie (London : Aquamarine ; Lanham, Maryland : North American distributor, National Book Network, 2006)
A wonderfully tantalizing blend of rich aromas and tastes, Malaysian cooking fuses the distinctive flavors of South-east Asian food with Chinese and Indian influences. The result is a heady mixture of herbs and spices, sometimes cool, some fiery, but always in perfect harmony
Includes index
Keywords: Cooking, Malaysian; Cooking, Singaporean